The serials librarian (Haworth Press, 1976)
"The international quarterly journal of serials management."Current frequency: 8/year.Published: New York, NY, 1976- ; Binghamton, NY, 1991- 2008; Philadelphia : Taylor & Francis Group, 2009- .Has supplement: Monographic supplement to the Serials librarian, ISSN 0897-8409.